Near-transection of abdominal aorta due to stab injury: a case report - Bilchod, Suhas S.; Dakhani, Nawaz M.; Arkalgud, Deepak; Lamani, Yamanur P. (International Surgery Journal, 2020)
Abdominal vascular injuries are amongst the most lethal injuries encountered by modern day trauma and vascular surgeons. Penetrating injuries to aorta have a wide spectrum of presentation mortality being 50-70%. 38-year-old male presented to emergency department with stab injury to abdomen with a knife stuck in-situ. Patient was conscious with herniating bowel loops from stab site. Bilateral limbs had good pulsations and no neurological deficit. Patient was taken for emergency laparotomy and found to have complete jejunal transection with near transection of aorta with knife stuck in the vertebra. Primary repair of aorta was done with prolene 5-0 along with jejuno-jejunal anastomosis. Patient was transfused with 12 units of blood and 8 units of FFP. Postoperatively patient recovered well and was discharged on post-operative day (POD) 14 with good recovery and follow up was uneventful. Spectrum of penetrating aortic injuries varies from stable patients to severely exsanguinated in vicious cycle of shock, acidosis, coagulopathy and arrhythmias causing high mortality and morbidity. Our case had contained retroperitoneal hematoma with stable vitals and good general condition and due to early diagnosis and timely institution of surgery the patient survived and recovered uneventfully. All abdominal stab injuries are to be taken as having vascular injuries. Surgery has to be taken up as an integral part of resuscitation with quickest and most effective diagnostics along with lifesaving procedures to have lesser morbidity and mortality.